Mental Health of Pregnant and Postpartum Women During the Coronavirus Disease 2019 Pandemic: A Systematic Review and Meta-Analysis - Yan, Haohao; Ding, Yudan; Guo, Wenbin (Frontiers in Psychology, 2020)
Background: Prenatal and postnatal mental disorders can exert severe adverse influences on mothers, fetuses, and children. However, the effect of the coronavirus disease 2019 (COVID-19) pandemic on the mental health of pregnant and postpartum women remains unclear. Methods: Relevant studies that were published from January 1, 2019 to September 19, 2020 were identified through the systematic search of the PubMed, EMBASE, and Web of Science databases. Quality assessment of included studies, random-effects meta-analysis, sensitivity analysis, and planned subgroup analysis were performed. Results: A total of 23 studies conducted with 20 569 participants during the COVID-19 pandemic and with 3677 pregnant women before the COVID-19 pandemic were included. The prevalence rates of anxiety, depression, psychological distress, and insomnia among pregnant women during the COVID-19 pandemic were 37% (95% confidence interval [CI] 25%–49%), 31% (95% CI 20%–42%), 70% (95% CI 60%–79%), and 49% (95% CI 46%–52%), respectively. The prevalence of postpartum depression was 22% (95% CI 15%–29%). Multigravida women and women in the first and third trimesters of pregnancy were more vulnerable than other women. The assessment of the associations between the COVID-19 pandemic and mental health problems revealed that the pooled relative risks of anxiety and depression in pregnant women were 1.65 (95% CI: 1.25–2.19) and 1.08 (95% CI: 0.80–1.46), respectively. Conclusions: The prevalence rates of mental disorders among pregnant and postpartum women during the COVID-19 pandemic were high. Timely and tailored interventions should be applied to mitigate mental problems among this population of women, especially multigravida women and women in the first and third trimesters of pregnancy.